Oracle Enterprise manager 10g grid control handbook - Gruyter, Werner De (McGraw-Hill Education, 2010)
Centralize and simplify enterprise infrastructure administration using the detailed information contained in this Oracle Press guide. Oracle Enterprise Manager 10g Control Handbook shows you how to implement a grid-based management system and maintain on-demand access to critical services. Develop rollout plans, configure hardware and software, deploy targets and agents, control access, and distribute business reports. This authoritative resource also explains how to generate reliable backups, implement top-down performance monitoring, and maximize system availability.